Interlayer Coupling Induced Infrared Response in WS2/MoS2 Heterostructures Enhanced by Surface Plasmon Resonance. (6th April 2018) - Wang, Guichao; Li, Liang; Fan, Weihao; Wang, Renyan; Zhou, Shasha; Lü, Jing‐Tao; Gan, Lin; Zhai, Tianyou
Abstract: Infrared light detection is generally limited by the intrinsic bandgap of semiconductors, which suppresses the freedom in infrared light photodetector design and hinders the development of high‐performance infrared light photodetector. In this work, for the first time infrared light (1030 nm) photodetectors are fabricated based on WS2 /MoS2 heterostructures. Individual WS2 and MoS2 have no response to infrared light. The origin of infrared light response for WS2 /MoS2 comes from the strong interlayer coupling which shrinks the energy interval in the heterojunction area thus rendering heterostructures longer wavelength detection ability compared to individual components. Considering the low light absorption due to indirect bandgap essence of few layers WS2 /MoS2 heterostructures, its infrared responsivity is further enhanced with at most ≈25 times but the fast response rate is maintained via surface plasmon resonance (SPR). Such an interlayer coupling induced infrared light response and surface plasmon resonance enhancement strategy paves the way for high‐performance infrared light photodetection of infinite freedom in design. Abstract : Infrared photodetectors based on WS2 /MoS2 heterostructures are realized for the first time. WS2 and MoS2 show no infrared (1030 nm) response alone but strong interlayer coupling shrinks the energy interval in the heterojunction area, rendering heterostructures with longer wavelength detection ability compared to the individual components. Furthermore, the infrared (1030 nm) responsivity of the heterostructures is enhanced by ≈25 times via surface plasmon resonance.